An Interview with Dr. Raywat Deonandan about COVID-19 Misinformation - Intahchomphoo, Channarong; Brown, Michelle (Université d'Ottawa | University of Ottawa, 2020)
Dr. Raywat Deonandan is an Associate Professor at the Interdisciplinary School of Health Sciences, University of Ottawa. This interview was conducted by phone on September 3rd, 2020.